Trends in area, yield and production of major oilseeds Punjab: district-wise analysis - Kaur, Avaneet and Grover, D.K. (Agricultural Situation in India)
Due to the advent of green revolution in mid-sixties, the agricultural landscape has undergone a major changes from a well diversified cropping pattern to monoculture of paddy-wheat rotation in the state of Punjab and resulting into various ecological, hydrological, environmental degradations. In the present study, efforts have been made to examine the area, production and yield treads of various oilseeds, during the last five decades in Punjab. Statistical tools such as mean coefficient of variance, compound growth rate and student$1 (Bs t-test were applied to check the significant different in the trends in area, production and yield using compound growth rates. - Reproduceds
Keywords: Oilseeds, Cultivation, Green revolution - India